The Moderating Effect of Smart Tourism Technologies: Tourist Destination Loyalty Success in Dili (Timor Leste) - Ximenes, Mateus; Mustika, Hindah; Pujiwat, Rutma; Abbas, Ansar (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
The research focuses on testing and analyzing the influence of several components of tourist destination loyalty, namely tourist satisfaction, experience quality, and smart tourist technologies which as a moderator variable. The research uses a quantitative method to see the influence of each variable. The respondents of the research are from various backgrounds, with a total of 317 visitors (210 women) and (107 men) who have visited tourist attractions of places historical locations in Dili (Timor Leste). The processing data use SEM-PLS, and the results of processing data show that all hypotheses significantly influence (direct) and (indirect hypotheses: smart tourist satisfaction is able to be a good moderator variable between experience quality and tourist satisfaction). The theory implication as a development of behavior and smart technologies theory, as well as the practical implication of being a strategic policy maker for stakeholders. The novelty of the research is that experience quality is in the form of physical and non-physical experiences that have positive emotions that are felt and shared with everyone so that there is satisfaction for visitors and tourist attractions.